Critical Thinking Skills of Junior High School Students in Environmental Content: A Gender-Based Profile - Baiq Fatmawati; Husnul Khotimah (Postgraduate, University of Mataram, 2025)
This study aims to analyze the critical thinking skills of junior high school students in environmental pollution materials based on gender differences. The research used a descriptive-comparative design with 60 Grade VII students at MTs Raudhatul Azhar, East Lombok, selected purposively. Data was collected using an essay test consisting of four indicators of critical thinking: elementary clarification, advanced clarification, information gathering, and inference. Descriptive results showed that female students had higher average scores (M = 77.8; SD = 5.4) than male students (M = 68.9; SD = 6.1). Independent t-test results confirmed significant differences in all indicators (p < 0.05), indicating that female students demonstrated higher levels of critical thinking skills. The results highlight the importance of developing learning strategies that are sensitive to gender characteristics to support the equitable development of students’ critical thinking skills.